Pengaplikasian Teknologi Digitalisasi dan Penataan Ruang sebagai Kunci Peningkatan Pemasaran Museum Mandala Bhakti Semarang - Muhamad Maulidul Atiq Fardani; Achmad Fikri Ash Shofi Billah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The Mandala Bhakti Museum in Semarang plays a vital role as a historical tourism destination that represents the struggles of the Indonesian people. However, one of the main challenges in managing this museum is attracting visitors, especially the younger generation. This study aims to evaluate and implement digital technology and spatial arrangement as strategies to enhance the museum's appeal and marketing. These strategies include the development of virtual tour applications, digitization of museum collections, optimization of social media usage, and redesigning spaces to be more interactive and engaging for visitors. The research employs a qualitative approach with data collected through interviews, observations, and literature reviews. The findings reveal that the utilization of digital technologies such as augmented reality (AR) and various digital platforms significantly boosts the museum's appeal. Additionally, creative spatial design provides visitors with a more immersive and enjoyable experience. Through these strategies, the Mandala Bhakti Museum in Semarang can reach a broader audience, increase visitor numbers, and strengthen its position as a relevant historical tourism destination in the digital era.